1979
DOI: 10.1111/j.1365-2621.1979.tb08514.x
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Corn: Varietal and Developmental Differences in Amino Acid Content and Composition of Grain

Abstract: Grain of three varieties of hybrid sweet corn was harvested and analyzed at approximately 15, 30, 45 and 60 days after pollination to establish variation in composition and amino acid content among varieties and during course of grain maturation. In all three varieties, percent protein content on a dry basis dropped markedly after 15 days post‐pollination but remained fairly constant at 12–13% during later development. Fat increased steadily from 3 to 7 or 8% (dry basis) in all varieties. Lysine content decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
3
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 3 publications
5
3
0
Order By: Relevance
“…Averaged over all inbreds, the protein concentration of sh2 corn (17.6%) was 30% higher than that of su1 corn ( 13.5%). The protein concentration of the su1 corn was similar to that reported by Sanderson et al (1979). sh2 kernels were significantly lighter than su1 kernels in six of the seven nearisogenic comparisons (Table 1).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Averaged over all inbreds, the protein concentration of sh2 corn (17.6%) was 30% higher than that of su1 corn ( 13.5%). The protein concentration of the su1 corn was similar to that reported by Sanderson et al (1979). sh2 kernels were significantly lighter than su1 kernels in six of the seven nearisogenic comparisons (Table 1).…”
Section: Resultssupporting
confidence: 80%
“…Little information is available on variation in protein concentration in sweet corn. Sanderson et al (1979) studied the changes in endosperrn protein concentration in three sugary-1 (su1) hybrids over time. They found hybrid protein concentration to be ≈ 20% at 15 days after pollination (DAP).…”
mentioning
confidence: 99%
“…It has been reported that sweet corn is one of the most important sources of dietary protein among vegetables because of its relatively high protein concentration (3.5 g/100 g edible portion) (Goldman and Tracy, 1994). Our protein content results are similar to the results of Sanderson et al (1979) and Goldman and Tracy (1994).…”
Section: Sugar Starch and Protein Content Of Fresh Frozen And Cannesupporting
confidence: 82%
“…[Because it is impractical to dissect out enough germs to do the relevant experiment, we have not determined if the addition of a small amount of endosperm improves an all-germ diet, as is the case with Tribolium confusum feeding on wheat seeds (Waldbauer & Bhattacharya, 1973).] [These data are from analyses of mature dent corn kernels, but the proportions are probably similar to those in young sweet corn kernels (Sanderson et al, 1979;Shannon & Creech, 1973).] The nutritional basis of this increase in efficiency cannot be explained with the data on hand, but there is no doubt that the nutrient contents of maize germ and endosperm are vastly different.…”
Section: Discussionmentioning
confidence: 99%
“…Endosperm contains about 90/0 protein, 0.8~ oil and 87~ total carbohydrates (simple sugars plus starch); germ contains about 19% protein, 34~ oil and only 19% total carbohydrates (Earle et aL, 1946). [These data are from analyses of mature dent corn kernels, but the proportions are probably similar to those in young sweet corn kernels (Sanderson et al, 1979;Shannon & Creech, 1973).] In addition to these quantitative differences, there are also major qualitative differ-169 ences.…”
Section: Discussionmentioning
confidence: 99%